Use of Autoleukocyte, Labelled with {99m}Tc-Exametazine for Evaluation of Inflammatory Changes in Myocardium - Sazonova S. I. Svetlana Ivanovna; Lishmanov Yu. B. Yury Borisovich; Iljyushenkova Yu. N. Yuliya Nikolaevna; Batalov R. E.; Rogovskaya Y. V. (Radiation Technologies in Medicine, 2015)
Title screen